The association of individual food security status with women's political participation, labor-force participation, and reproductive health : A cross-sectional analysis of gendered structural inequality in the League of Arab States - Dean, Wesley Raymond; Sheikomar, Olfat; Ghattas, Hala; el-Husseini, Rola ; 0000-0002-4164-4406; Sahyoun, Nadine (Social Science and Medicine, 2025)
This article applies a conceptual framework based on multilevel theories of gender inequality to examine individual-level food insecurity (FI) outcomes in the League of Arab States (LAS). We conceptualize FI as an embodied waypoint on a discriminatory cycle incorporating material and cultural practices that function at macro-, situational-, and individual-levels. Using data drawn from the Gallup World Poll representing a sample of non-institutionalized, aged 15 and above respondents, FAO's Food Insecurity Experience Scale, the UNDP's Gender Inequality Index, and the Varieties of Democracy (V-Dem) Project, we provide cross-sectional evaluations of the associations between gender-related variables and individual-level measures of the experience of FI for both women and men for the LAS, and for states stratified by Human Development Index. National measures of gender inequality were significantly associated with FS status for both men and women, including women's reproductive health (adolescent births and maternal mortality), parliamentary representation, and labor force participation. Regression models run separately for each measure had explanatory power, and addition of each level substantially improved Pseudo R2s. This suggests national-level policies on FS should address national-level gender inequalities and broaden women's substantive representation in governance, promising further value in exploring FI as an embodied health disparity among women and men, through the multilevel framework of gendered structural inequality.
Keywords: Adolescent birth rate; Food insecurity; Gendered social structure; Health inequities; labor-force participation; League of arab states; Maternal mortality; Political participation